Impact of Social Forestry Policy On Forest Fires in Bayung Lencir District, Musi Banyuasin Regency - Ahmad Zamhari (Journal of Global Sustainable Agriculture, 2025)
Social Forestry Program (PS) is a national initiative aimed at providing legal access for local communities and indigenous groups to manage state forests through schemes such as Village Forests, Community Forests, People's Plantations, Customary Forests, and Forest Partnerships. The goal of social forestry is to improve economic welfare while maintaining the forest ecosystem functions. In the Bayung Lencir District, Musi Banyuasin Regency, there is a social forestry area of approximately 22,093 hectares, consisting of 15 social forestry permits involving 2,154 households. One of the obligations of social forestry permit holders is to protect their area from forest fires. However, from 2014 to 2024, an average of 49 forest fire hotspots occurred annually, with the peak of forest fires occurring during the El Nino years of 2015 (235 hotspots in LPHD Kepayang) and 2019 (169 hotspots in LPHD Muara Merang). These figures reflect the weak capacity for fire mitigation within social forestry groups, limited technical and financial resources, and the lack of policy integration into regional planning. Policy analysis was conducted using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, focusing on policies for improving fire mitigation capacity and firefighting infrastructure, collaboration and partnership policies, policies for increasing village fund utilization, strengthening national policy, and policies for climate change adaptation and disaster mitigation. The policy selection alternatives were evaluated using a priority table for policy alternatives. The prioritized policy recommendation is the improvement of fire mitigation capacity and firefighting infrastructure. To support this policy, a Logic Model Analysis was performed.